A 3D pseudo-continuous arterial spin labeling study of altered cerebral blood flow correlation networks in mild cognitive impairment and Alzheimer's disease - Li, Meng; Zhu, Tianjia; Kang, Yan; Qi, Shouliang (Frontiers in Aging Neuroscience, 2024)
Objective: To investigate the abnormalities of the three-dimensional pseudo-continuous arterial spin labeling (3D PCASL) based cerebral blood flow (CBF) correlation networks in mild cognitive impairment (MCI) and Alzheimer's disease (AD).Methods: 3D PCASL images of 53 cognitive normal (CN) subjects, 43 subjects with MCI, and 30 subjects with AD were acquired from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. Whole brain CBF maps were calculated using PCASL and proton density-weighted images (PDWI). The 246 regional CBF values including the cortex and subcortex were obtained after registering the Brainnetome Atlas to the individual CBF maps. The Pearson correlation coefficient between every two regions across subjects was calculated to construct the CBF correlation network. Then the topologies of CBF networks at global properties (global network efficiency, clustering coefficient, characteristic path length, and small-world properties), hub regions, nodal properties (betweenness centrality, BC), and connections were compared among CN, MCI, and AD. Significant changes in the global and nodal properties were obtained by conducting permutation tests, and connections with significant differences survived after the z statistic and false discovery rate (FDR) correction.Results: CBF correlation networks of CN, MCI, and AD all showed small-world properties. Compared with CN, global efficiency decreased significantly in AD. Significant differences in nodal 3D PCASL-based CBF correlation networks properties and a loss of hub regions are in the middle temporal lobe in both MCI and AD. In the frontal lobe, BC reduced in MCI while that increased in the occipital lobe in AD. The identified altered hub regions with significant differences in MCI and AD were mainly distributed in the hippocampus and entorhinal cortex. In addition, disrupted hub regions in AD with significantly decreased connections were mainly found in the precuneus / posterior cingulate cortex (PCC) and hippocampus-cortical cortex.Conclusions: Noninvasive 3D PCASL-based CBF correlation networks can reflect the changes in the topological organization in subjects with MCI and AD, and the observed disruption in the topological organization may underlie the cognitive decline in MCI and AD.